Enhancing Narrative Writing Skills in Fifth-Grade Students through Audio-Visual Learning and Independent Learning Approach - Febriari Triswanti; Gusti Yarmi; Aminudin Zuhairi (Universitas PGRI Adi Buana Surabaya, 2023)
This study aims to measure the effect of Learning Media and Learning Independence on the Narrative Writing Ability of Grade V Students in Gugus II, Cempaka Putih District. The experimental method was used with a target population of 261 students. The sample consisted of 43 students who were given Animated Film Learning Media, divided into 22 students of high learning independence and 21 students of low learning independence, and 43 students who were given Film Learning Media, divided into 22 students of high learning independence and 21 students of low learning independence. The results showed that Narrative Writing Ability was higher in the group given Animated Film Learning Media than in Film Learning Media (Fhitung = 13.018 > Ftabel = 3.96). Narrative Writing Ability is also higher in students with high independence than low independence (Fcount = 11.922 > Ftable = 3.96). There is an interaction between learning media and independence in students' narrative writing ability (Fcount = 61.052 > Ftable = 3.96). This research can potentially improve narrative writing learning in Class V elementary schools in Gugus II Cempaka Putih District